Response to pneumococcal vaccination in multiple myeloma. (30th May 2019) - Renaud, Loïc; Schraen, Susanna; Fouquet, Guillemette; Guidez, Stephanie; Demarquette, Hélène; Nudel, Morgane; Cayssials, Emilie; Bories, Claire; Herbaux, Charles; Systchenko, Thomas; Faucompré, Jean‐Luc; Machet, Antoine; et al.
Abstract: Background: Streptococcus pneumoniae infection causes morbidity and mortality in multiple myeloma patients. Pneumococcal vaccination is commonly given to immunocompromised myeloma patients; however response data are sparse. Here, we present longitudinal response data to pneumococcal vaccination in multiple myeloma patients. Method: Twenty‐eight multiple myeloma patients were included, 25 of whom were newly diagnosed. All the patients received two vaccines Prevnar13® and Pneumo23®. Serotype‐specific IgG was measured by ELISA for all 23 vaccine serotypes at baseline, and then sequentially at different time points postvaccination until treatment ended. Response to vaccination is available for 20 patients. The primary endpoint was the incidence rate of patients who obtained an isotype response serum concentration after vaccination. Secondary endpoints included detailed isotype increase, time to first increase, further assessment of a decreased anti‐pneumococcal serum concentrations following treatment including autologous stem cell transplantation (ASCT), rate of infection with a special attention to pneumococcal infection. Results: The median age was 66 years and the male to female ratio was 0.6. Anti‐pneumococcal capsular polysaccharide (anti‐PCP23) IgG, IgG2, IgA, and IgM responses were detected within 1 week postvaccination. Response to at least one subtype of antibody was obtained in 85% (n = 17) of patients, for at least two subtypes in 65% (n = 13), for at least three subtypes in 55% (n = 11), and 2 patients responded to all four subtypes. The median increase in the concentration of anti‐PCP23 isotypes was threefold following vaccination, with the highest increase observed when Pneumo23® was given more than 30 days after Prevnar13®. The anti‐pneumococcal geometric mean concentration decreased significantly for all subtypes over time independently of treatment approaches. Conclusion: Myeloma has the ability to demonstrate a response to pneumococcal vaccine, independently of preexisting hypogammaglobulinemia and possibly of treatment‐induced immunodepression. We also observed a drop in the serum response overtime and following autologous transplantation. Further studies in larger sample are needed to understand the benefit of vaccination strategies in these patients. Abstract : Twenty‐eight multiple myeloma patients who received two vaccines Prevnar13® and Pneumo23® were included in this study. The median increase in the concentration of anti‐PCP23 isotypes was threefold following vaccination, with the highest increase observed when Pneumo23® was given followed by Prevnar13®. The result shows that myeloma has the ability to demonstrate a response to pneumococcal vaccine and patient should be vaccinated independently of preexisting hypogammaglobulinemia and possibly of treatment‐induced immunodepression.